Gambaran Indeks Eritrosit Pada Anak Jalanan Di Kota Yogyakarta - Hieronymus Rayi Prasetya; Titah Dewi Rahadian (LPPM STIKES Guna Bangsa, 2019)
The transportation sector has proven to be one of the causes of lead pollution in the air. Lead pollution is a result of vehicle fuel use. Lead is a metal that is very dangerous because it can accumulate in the body resulting in reduced production of erythrocytes and erythrocyte morphological abnormalities. Buskers have a risk of red cell Indices abnormalities due to exposure to vehicle exhaust gas every day. Buskers in the city of Yogyakarta carry out activities (busking) every day around trafficlight so that it will increase the risk of respiratory poisoning. The study was conducted by giving questionnaires to 32 respondents and the red cell Indices examination was performed using a hematology analyzer. The results showed that the average value of red cell Indices based on sex, age, duration of work, alcohol and cigarette consumption habits were still within normal limits (normocytic normochromic). There are no red cell Indices abnormalities (size and color) in buskers in Yogayakarta City